1991
DOI: 10.1152/jappl.1991.71.3.1015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal exercise on liver and skeletal muscle glycogen storage in pregnant rats

Abstract: To examine the effects of maternal exercise on liver and skeletal muscle glycogen storage, female Sprague-Dawley rats were randomly divided into control, nonpregnant runner, pregnant nonrunning control, pregnant runner, and prepregnant exercised control groups. The exercise consisted of treadmill running at 30 m/min on a 10 degree incline for 60 min, 5 days/wk. Pregnancy alone, on day 20 of gestation, decreased maternal liver glycogen content and increased red and white gastrocnemius muscle glycogen storage ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
14
2
Order By: Relevance
“…Results from several studies suggest that late pregnancy may increase skeletal muscle resting glycogen concentrations (17,18,28), and previous studies have implicated precontraction glycogen concentration as a regulator of contraction-induced glycogen depletion and glucose transport (15,22,23). Accord- ingly, we assessed glycogen levels and found that pregnancy was associated with a nonsignificant trend for 13% increase in resting glycogen concentrations in epitrochlearis muscles, a result similar to the data of Holness and Sugden (17,18).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Results from several studies suggest that late pregnancy may increase skeletal muscle resting glycogen concentrations (17,18,28), and previous studies have implicated precontraction glycogen concentration as a regulator of contraction-induced glycogen depletion and glucose transport (15,22,23). Accord- ingly, we assessed glycogen levels and found that pregnancy was associated with a nonsignificant trend for 13% increase in resting glycogen concentrations in epitrochlearis muscles, a result similar to the data of Holness and Sugden (17,18).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, isolated epitrochlearis muscles from pregnant and nonpregnant rats were stimulated to contract by the same stimulation protocol. In addition, insulin-stimulated glucose uptake was determined for epitrochlearis muscles so that the magnitude of pregnancy effects on the two major pathways for activating muscle glucose transport could be compared in the same study.Under resting conditions, skeletal muscle glycogen concentration is similar or higher for pregnant compared with nonpregnant rats (17,18,28). However, the effect of contractile activity on glycogen depletion during pregnancy has apparently not been previously reported.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…A cascade of hormonal events increases maternal blood glucose, decreases liver glycogen storage, elevates liver glucose release74 and increases maternal insulin levels 75. This increases insulin resistance in skeletal muscle76 and thus decreases maternal utilisation of glucose in peripheral tissues, which leaves more maternal glucose for fetal use 77.…”
Section: Pregnancymentioning
confidence: 99%
“…In nonpregnant females, circulating glucose initially declines in the first 20 minutes of exercise, followed by a return to preexercise levels with longer duration exercise as a result of liver glycogen breakdown/release or glycogenolysis. 18 However, pregnancy is associated with reduced liver glycogen storage, 19 thus maternal glucose concentrations may remain depressed withlongerdurationand/or higher intensity exercise. 16 Indeed, Soultanakis et al 17 examined the effect of 60 minutes of moderate intensity exercise and found that circulating glucose concentrations in pregnant women declined faster and reached lower levels than nonpregnant women.…”
Section: Hormone and Substrate Adaptations To Prenatal Exercisementioning
confidence: 99%